2009
DOI: 10.1142/s0218348x0900451x
|View full text |Cite
|
Sign up to set email alerts
|

Gaps in the Ratios of the Spectra of Laplacians on Fractals

Abstract: In contrast to the classical situation, it is known that many Laplacian operators on fractals have gaps in their spectrum. This surprising fact means there can be no limit in the Weyl counting formula and it is a key ingredient in proving that the convergence of Fourier series on fractals can be better than in the classical setting. Recently, it was observed that the Laplacian on the Sierpinski gasket has the stronger property that there are intervals which contain no ratios of eigenvalues. In this paper we gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Thus it is of great interest to know whether similar operators exist for products of fractals other than SG. In fact [15] shows that this is the case for VS 2 and VS 3 . Also [9] investigates this question for a variant of the SG type fractal.…”
Section: Ratio Gapsmentioning
confidence: 81%
“…Thus it is of great interest to know whether similar operators exist for products of fractals other than SG. In fact [15] shows that this is the case for VS 2 and VS 3 . Also [9] investigates this question for a variant of the SG type fractal.…”
Section: Ratio Gapsmentioning
confidence: 81%
“…for the appropriate domains, and are extended by the polynomial representation everywhere else. An interesting feature of this result is that the function R(z) is given by a rational function which has disconnected real Julia set (see [26,27]) because R(z) has poles in the convex hull of its Julia set. One implication of this is that the spectrum of the renormalized limit of ∆ n , ∆ has gaps in the sense of [70], which implies that the Fourier series of continuous functions converge uniformly on K.…”
Section: Remark 22 Note That the Spectral Dimensionmentioning
confidence: 99%
“…Recently there has been considerable interest in Laplace operators with exotic spectral properties. For instance, large spectral gaps imply uniformly convergent Fourier expansions on fractals, see [70], and oscillations in the spectrum, see [2,4,26,27,12,40,42,41,43,50, and references therein]. However there had not been any infinite families of fractals with complicated spectra which can be computed.…”
mentioning
confidence: 99%
“…Strichartz [36] showed that the existence of spectral gaps implies better convergence of Fourier series. Rigorous proofs for the existence of spectral gaps have been obtained for only a limited number of fractals, such as the Sierpiński gasket and the Vicsek set (see [9,19,38]).…”
Section: Introductionmentioning
confidence: 99%